Plasma level of ADAMTS-13 in maintenance hemodialysis patients and its relation to arteriovenous fistula thrombosis - Saja Hammadi Fahad; Najiha Ahmed Ameen (Diyala Journal of Medicine, 2023)
Background: End-stage renal disease is the final stage of chronic kidney disease in which irreversible deterioration in renal function occur and the body fails to maintain fluid and electrolyte balance, this need regular hemodialysis (HD) a process that removes accumulated solute from a patient with near-total renal function loss. Arteriovenous fistula (AVF) is the vascular access of choice for patients who require hemodialysis. AVF thrombosis is a major issue in hemodialysis  patients, which increase their morbidity and  lessen HD efficiency.